Motion and form vision in typical and atypical adult readers - Johnston, R. (2017)
Poor reading in adults is often associated with developmental dyslexia, especially for adults that have average, or above average, intelligence and no history of ocular ill health, social deprivation, or other learning difficulties. Developmental dyslexia is primarily associated with poor phonological decoding skills, but evidence suggests that there is also a visual perception deficit. In particular, it has been reported that individuals with dyslexia have difficulty integrating local motion, but not local form, cues into a global percept. However, current theories proposed to explain this visual impairment, cannot fully accommodate the perceptual abilities of readers with dyslexia. The aim of this thesis is to investigate the origin of visual impairment in poor readers, including those with dyslexia.